Kecerdasan Spiritual sebagai Paradigma Baru Penentu Keberhasilan Seseorang - Gita Laelatul Qodriah (UIN Sunan Gunung Djati Bandung, 2023)
This study aims to discuss spiritual intelligence as a new paradigm determining one's success. This research uses a qualitative approach by applying the literature study method. The formal object of this study is the theory of spiritual intelligence, while the material object is a new paradigm. The scope of research is a person's success. The results and discussion in the research show that a person's success can be determined by spiritual intelligence, because spiritual intelligence is the main intelligence between intellectual intelligence and emotional intelligence. Thus giving rise to a new paradigm in intelligence. This study concluded that spiritual intelligence is the main intelligence between intellectual and emotional intelligence, although these three intelligences are related to each other. However, the role of spiritual intelligence is very important because it is believed to be able to function intellectual and emotional intelligence, thus making humans called complete humans intellectually, emotionally and spiritually. This research recommends that institutions and organizations that are closely related to spiritual intelligence to conduct research on new paradigms regarding one's success.